2007
DOI: 10.1016/j.immuni.2007.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Pannexin-1-Mediated Recognition of Bacterial Molecules Activates the Cryopyrin Inflammasome Independent of Toll-like Receptor Signaling

Abstract: Cryopyrin is essential for caspase-1 activation triggered by Toll-like receptor (TLR) ligands in the presence of adenosine triphosphate (ATP). However, the events linking bacterial products and ATP to cryopyrin remain unclear. Here we demonstrate that cryopyrin-mediated caspase-1 activation proceeds independently of TLR signaling, thus dissociating caspase-1 activation and IL-1beta secretion. Instead, caspase-1 activation required pannexin-1, a hemichannel protein that interacts with the P2X(7) receptor. Direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
417
3
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 480 publications
(451 citation statements)
references
References 49 publications
(84 reference statements)
24
417
3
4
Order By: Relevance
“…33,51 ATP binds to the purinergic receptor P2X7, resulting in the opening of the protein channel pannexin-1. 52 This allows potassium efflux, inflammasome activation and ATP release. 53 However, it has been proposed that the pore formation following pannexin-1 recruitment could allow cytosolic access to microbial products, such as lipopolysaccharide (LPS), which can directly activate the inflammasome.…”
Section: Genetics Of the Inflammasomes In Human Pathologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…33,51 ATP binds to the purinergic receptor P2X7, resulting in the opening of the protein channel pannexin-1. 52 This allows potassium efflux, inflammasome activation and ATP release. 53 However, it has been proposed that the pore formation following pannexin-1 recruitment could allow cytosolic access to microbial products, such as lipopolysaccharide (LPS), which can directly activate the inflammasome.…”
Section: Genetics Of the Inflammasomes In Human Pathologiesmentioning
confidence: 99%
“…53 However, it has been proposed that the pore formation following pannexin-1 recruitment could allow cytosolic access to microbial products, such as lipopolysaccharide (LPS), which can directly activate the inflammasome. 52 Although it is unclear whether the pore width would be sufficient to allow entrance of such microbial-derived molecules.…”
Section: Genetics Of the Inflammasomes In Human Pathologiesmentioning
confidence: 99%
“…Chez l'homme, la famille des ALR comporte quatre membres : AIM2, IFI16 (interferon -inducible protein 16), MNDA (myeloid cell nuclear differentiation antigen), et IFIX (interferon inducible protein X) [9]. L'extrémité carboxy-terminale des ALR contient un domaine de liaison à l'ADN double-brin appelé HIN200.…”
Section: Les Récepteurs Alrunclassified
“…L'activation de ce récepteur membranaire entraîne l'ouverture d'un canal protéique (la pannexine) et un efflux d'ions potassium hors de la cellule. La diminution de la concentration intracellulaire en potassium induit un changement de conformation de NLRP3 et l'activation de l'inflammasome NLRP3 [15][16][17]. De la même manière, des variations de l'homéostasie calcique pourraient participer à la détection des dommages membranaires via l'activation de NLRP3 [18].…”
Section: L'activation De Nlrp3unclassified
“…Pelegrin and Surprenant have shown that inhibition of pannexin-1 can block caspase-1 activation even in the presence of potassium efflux suggesting that it functions downstream of potassium's efflux [34]. Interestingly, pannexin-1 may also function to bring PAMPs into the cytosol for pathogen sensing [35].…”
Section: Macrophages Less Responsive Than Monocytes To P2x 7 Agonistsmentioning
confidence: 99%